Functional screening of salt tolerance genes from a halophyte Sporobolus virginicus and transcriptomic and metabolomic analysis of salt tolerant plants expressing glycine-rich RNA-binding protein. (January 2019) - Tada, Yuichi; Kawano, Ryuichi; Komatsubara, Shiho; Nishimura, Hideki; Katsuhara, Maki; Ozaki, Soichi; Terashima, Shin; Yano, Kentaro; Endo, Chisato; Sato, Muneo; Okamoto, Mami; Sawada, Yuji; et al.
Highlights: We screened salt tolerant Arabidopsis lines expressing Sporobolus virginicus cDNA. We obtained two salt tolerant lines including SvGRP1 and SvGRP2. Transcriptomic analysis revealed up and downregulation of genes in the SvGRP1 line. Metabolomics analysis revealed metabolites potentially involved in salt tolerance. Color should be used for figures in only online but not in print. Abstract: Sporobolus virginicus is a halophytic C4 grass found worldwide, from tropical to warm temperate regions. One Japanese genotype showed a salinity tolerance up to 1.5 M NaCl, a three-fold higher concentration than the salinity of sea water. To identify the key genes involved in the regulation of salt tolerance in S. virginicus, we produced 3500 independent transgenic Arabidopsis lines expressing random cDNA from S. virginicus and screened 10 lines which showed enhanced salt tolerance compared with the wild type in a medium containing 150 mM NaCl. Among the selected lines, two contained cDNA coding glycine-rich RNA-binding proteins (SvGRP1 and SvGRP2). This is the first reports on the function of GRPs from halophytes in salt tolerance though reports have shown GRPs are involved in diverse biological and biochemical processes including salt tolerance in Arabidopsis and some other glycophytes. Transcriptomic analysis and GO enrichment analysis of SvGRP 1-expressing Arabidopsis under salt stress revealed upregulation of polyol and downregulation of glucosinolate and indole acetic acid biosynthesis/metabolic pathways. Metabolomic analysis of the SvGRP1 -transformant suggested that the increase in 3-aminoppropanoic acid, citramalic acid, and isocitric acid content was associated with enhanced salt tolerance. These findings could provide novel insight into the roles of GRPs in plant salt tolerance.